2019
DOI: 10.1111/idj.12415
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of oral health-related quality of life as a function of non-invasive treatment with high-fluoride toothpastes for root caries lesions in community-dwelling elderly

Abstract: Non-invasive treatment for RCLs in community-dwelling elders appears to cause a positive impact on OHRQoL. Better OHRQoL was associated with higher socio-economic status and educational level. No significant differences were detected regarding the fluoride concentration in the dentifrices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
2
0
0
Order By: Relevance
“…This was similar to the finding by Leon et al, where the use of fluorides in management of caries led to a positive impact on OHRQoL. 32 The role of fluoride within the oral cavity helps in the formation of fluorapatite which reduces the solubility of hydroxyapatite crystals during acid attack and helps prevent caries. 33,34 Furthermore, fluoride also inhibits bacterial enzyme activities, thus reducing acid production and preventing the dissolution of the oral tissues, thus leading to improved oral health outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…This was similar to the finding by Leon et al, where the use of fluorides in management of caries led to a positive impact on OHRQoL. 32 The role of fluoride within the oral cavity helps in the formation of fluorapatite which reduces the solubility of hydroxyapatite crystals during acid attack and helps prevent caries. 33,34 Furthermore, fluoride also inhibits bacterial enzyme activities, thus reducing acid production and preventing the dissolution of the oral tissues, thus leading to improved oral health outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…This study found the use of fluoride toothpaste among ECDs to be a protective factor in lowering the OHIP score. This was similar to the finding by Leon et al, where the use of fluorides in management of caries led to a positive impact on OHRQoL [32]. The role of fluoride within the oral cavity helps in the formation of fluorapatite which reduces the solubility of hydroxyapatite crystals during acid attack and helps prevent caries [33,34].…”
Section: Discussionsupporting
confidence: 80%